THE POPULATION BIOLOGY OF BLUE SWIMMING CRAB Portunus pelagicus (Linnaeus, 1758) DURING OVERFISHING CONDITIONS IN EAST LAMPUNG WATERS - Indra Gumay Yudha; Nadya Andriani; Herman Yulianto; Rachmat Caesario; Putu Cinthia Delis (Universitas Mataram, 2025)
Blue swimming crab (BSC) is one of Lampung's main export fisheries commodities. The catch of BSC by fishermen in East Lampung waters is becoming more intensive and increasing from year to year, so it is a concern that it will threaten the sustainability of the stock. This research aimed to analyze the biology of several populations of BSC in East Lampung waters during overfishing conditions. Population biology data on BSC analyzed included growth rate, size at first caught, recruitment patterns, sex ratio, fishing mortality, exploitation level, and a potential spawning ratio. The analyzed data originated from BSC caught by crab net fishermen in East Lampung landed at TPI Kuala Penet and TPI Muara Gading Mas for 1 year (August 2019-June 2020), totaling 35,322 samples consisting of 20,586 males and 14,736 females. The research showed that the level of crab utilization had an E value of 0.71 per year. In these overfishing conditions, it was known that the growth of crabs in these waters was following the equation of CWt= 191,6x[1-e-130(t-(-0,073))]. The carapace width of BSC caught for the first time (Lc) was 119 mm (male) and 123 mm (female) with a sex ratio (M: F) that varied every month between 1:1 and 2:1. Recruitment occurred throughout the year. The SPR was slightly under 20% indicating that overfished conditions had caused the potential for the crab to spawn in an unsustainable condition.